CAPACITY BUILDING FOR WOMEN MSMEs: TRAINING ON THE PREPARATION OF FINANCIAL STATEMENTS AND FINANCIAL HEALTH ANALYSIS FOR EFFECTIVE BUSINESS DECISION-MAKING - Rahmawati, Teti; Jumantini, Entin; Nurhasanah, Ade; Poornawan, Defichril Hidah; Anwar, Khairul (Yayasan Education and Social Center, 2025)
The COVID-19 pandemic has a significant impact on the sustainability of MSMEs, especially those managed by women in Pajambon Village, Kuningan Regency. Limitations in the preparation of financial statements and business health analysis are the main challenges faced by female MSME actors in making effective business decisions. This service program aims to increase the capacity of women MSMEs through training in the preparation of financial statements and financial health analysis. The method used is Participatory Action Research (PAR) which involves socialization, technical training, hands-on practice, and the application of digital technology in the form of Android-based financial applications. The results of the training showed that participants improved their skills in compiling financial statements accurately and systematically, analyzing business health, and utilizing financial software to improve the efficiency of financial management. Participants were also able to identify business opportunities and risks through more structured financial data analysis. This program is expected to strengthen the competitiveness of women MSMEs in Pajambon Village, increase business resilience, and encourage local economic growth after the pandemic